2019
DOI: 10.3390/toxins11070424
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Characteristics and Antimicrobial Resistance Profiles of Shiga Toxin-Producing Escherichia coli Isolates from Humans in South Africa: 2006–2013

Abstract: Shiga toxin-producing Escherichia coli (STEC) isolates (N = 38) that were incriminated in human disease from 2006 to 2013 in South Africa were characterized by serotype, virulence-associated genes, antimicrobial resistance and pulsed-field gel electrophoresis (PFGE). The isolates belonged to 11 O:H serotypes. STEC O26:H11 (24%) was the most frequent serotype associated with human disease, followed by O111:H8 (16%), O157:H7 (13%) and O117:H7 (13%). The majority of isolates were positive for key virulence-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…Thus, in this study, we investigated the presence of VFs in E. coli strains to broaden the knowledge of the properties of E. coli strains isolated from diverse sources. Recent epidemiological studies have revealed that the STEC serotypes O26, O103, O111, O145, and O157 are highly related to human infections (they may account for up to 80% of human STEC infections) [8] and our results are in agreement with reports from other countries describing the high pathogenic potential of strains associated with these serogroups [2]. The presence of non-LEE effector genes encoded by O-island O1-71 is highly attributed to strains that were often involved in outbreaks and serious disease in humans [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, in this study, we investigated the presence of VFs in E. coli strains to broaden the knowledge of the properties of E. coli strains isolated from diverse sources. Recent epidemiological studies have revealed that the STEC serotypes O26, O103, O111, O145, and O157 are highly related to human infections (they may account for up to 80% of human STEC infections) [8] and our results are in agreement with reports from other countries describing the high pathogenic potential of strains associated with these serogroups [2]. The presence of non-LEE effector genes encoded by O-island O1-71 is highly attributed to strains that were often involved in outbreaks and serious disease in humans [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…From these findings, it seems that STEC strains carrying the stx1 gene are more often confronted than those carrying stx2. Possession of OI-43/48, OI-71, and non-LEE effectors genes together with stx2, eae and a whole plasmid is the hallmark of highly virulent STEC strains that are frequently associated with outbreaks and serious diseases such as hemorrhagic colitis (HC) and HUS [8]. Since the carriage of combinations of stx genes has been correlated with severity of the disease, the stx gene profile provides us an overview of the pathogenic potential of these STEC strains from diverse sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations